Prevalence of Tobacco Use and Successful Tobacco Quitting among Persons of Kageshwori-Manohara Municipality in Kathmandu, Nepal (Nepal Medical College Journal, 2025)
Tobacco use is the leading modifiable behavioural risk factor contributing to non-communicable diseases and preventable deaths. The most effective way for tobacco users to avoid or minimize the harmful effects is to quit tobacco use. This study aimed to determine the prevalence of tobacco use and successful tobacco quitting among persons aged 15 years and above. A community based quantitative cross-sectional study was conducted among 300 persons (m=191, f=109) in Bhadrabas area of Kageshwori-Manohara Municipality from September 2023 to February 2024. Participants were selected using simple random sampling technique. A semi-structured questionnaire based on the WHO STEPS survey questionnaire was used during the face-to-face interviews to collect the data. Almost half of the participants 142 (47.3%) were ever tobacco users and 121 (40.3%) were current tobacco users. Among ever tobacco users, majority of the respondents used smoked tobacco 122 (85.9%) and only 20 (14.1%) of them used smokeless tobacco. More than three fourth of the ever tobacco users 112 (78.9%) used cigarette (filtered & non-filtered) and mean age of initiation of tobacco use was 18.7±7.6 years. Out of 98 (69.0%) ever tobacco users who had tried to quit tobacco use, 21 (21.4%) had successfully quit the tobacco usage. Majority of the participants 279 (93.0%) reported that tobacco use was injurious to health but only 26 (18.3%) of ever tobacco users sought help to quit tobacco. Binary logistic regression models revealed that tobacco use was significantly associated with age, sex, marital status, ethnicity, education status, family type and comorbidities. Male participants (OR: 3.76, 95% CI: 1.98-7.12), married persons (OR:7.09, 95% CI: 2.10-23.86), persons without formal schooling (OR: 3.78, 95% CI: 1.75-8.15), participants belonging to nuclear family (OR: 1.99, 95% CI: 1.13-3.52) and unemployed participants (OR:1.73, 95% CI: 0.81-3.72) had increased odds of tobacco use. There was significant association between the type of family (p=0.026) and those who sought help to quit tobacco (p=0.011) with successful tobacco quitting. Strict policy implementation and counseling on cessation of tobacco usage as per WHO package of essential non-communicable (PEN) disease interventions should be carried out effectively to help the community people to quit the tobacco use.